A fuzzy uncertainty model for analytical and numerical homogenization of transversely fiber reinforced plastics - Caylak, Ismail; Penner, Eduard; Mahnken, Rolf (PAMM)

Model adaptivity on mean‐field and full‐field homogenization methods considering hierarchical unit cells - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

Damage simulation of fiber reinforced composites using mean‐field homogenization methods - Lenz, Peter; Mahnken, Rolf (PAMM)

Lehrbuch der Technischen Mechanik - Band 2: Elastostatik - Mahnken, Rolf

Full-Swing, High-Gain Inverters Based on ZnSnO JFETs and MESFETs - Lahr, Oliver; Zhang, Zhipeng; Grotjahn, Frank; Schlupp, Peter; Vogt, Sofie; von Wenckstern, Holger; Thiede, Andreas; Grundmann, Marius (IEEE Transactions on Electron Devices)
Metal-semiconductor and junction n-channel field-effect transistors (MESFETs and JFETs) have been fabricated on glass substrates using room temperature deposited amorphous zinc-tin oxide (ZTO) channel layers. Characteristics of transistors and inverter circuits are compared. Best FET devices exhibit ON-to- OFF current ratios over eight orders of magnitude, subthreshold swings as low as 250 mV/dec and field-effect mobilities of 5 cm 2 /Vs. Furthermore, all devices show long-term stability over a period of more than 200 days. Inverters fabricated using either MESFETs or JFETs exhibit remarkable peak gain magnitude values of 350 and voltage uncertainty levels as low as 260 mV for an operating voltage of 5 V. A Schottky diode FET logic (SDFL) approach is applied to shift the switching voltage which is a requirement for cascading of inverters for realization of ring oscillators.
Keywords: Electrical and Electronic Engineering; Electronic; Optical and Magnetic Materials

Mit Droste im Glashaus. Scherbensammlung

Terror(ismus), Theater und Tribunal: Ferdinand von Schirachs "Terror" und Joël Pommerats "La Révolution #1 – Wir schaffen das schon" - Morrien, Rita (#Engagement. Literarische Potentiale nach den Wenden)

Wegen Umbau geöffnet - Wüste Welt, Paterland und der Traum vom anderen Raum - Morrien, Rita (Mit Droste im Glashaus. Scherbensammlung)

Wasser und Stein, das Flüssige und das Feste - Morrien, Rita (Mit Droste im Glashaus. Scherbensammlung)

Polarization-Independent Depolarizer for Control and Supervisory Signals in Long-Haul Fiber Lines - Noé, Reinhold; Koch, Benjamin (Photonic Networks; 20th ITG-Symposium)

Low-Loss Arbitrary Polarization State Synthesizer for Quantum Key Distribution Purposes - Koch, Benjamin; Noé, Reinhold (Photonic Networks; 20th ITG-Symposium)

Kooperatives Arbeiten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven Unterricht in der Grundschule. Posterpräsentation auf der 54. Jahrestagung der Sektion Sonderpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE). „Sonderpädagogik und Bildungsforschung – Fremde Schwestern?“ - Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Effects of Interprofessional Collaboration in Inclusive Education of Pre-Service Primary School Teachers and Special Education Teachers on their Self-Concepts. Poster Presentation. ECER 2019 (European Conference on Educational Research). “Education in an Era of Risk – the Role of Educational Research for the Future“ - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Kooperativ Lernumgebungen für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule gestalten – ein Forschungs- und Entwicklungsprojekt zur Förderung von Grund- und Förderschullehrkräften (KLinG). Posterpräsentation auf der 28. Jahrestagung der Gesellschaft für Didaktik des Sachunterrichts e. V. (GDSU) - Mester, Theresa; Blumberg, Eva; Kirsch, Alexander; Hellmich, Frank; Schulze, Jan Roland; Hoya, Fabian Karl; Löper, Marwin Felix; Schwab, Susanne

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Preparing Pre-service Teachers’ Team-Teaching Processes in Inclusive Science Education in Primary Schools. Poster Presentation. Porto International Conference on Research in Education (ICRE) - Löper, Marwin Felix; Hoya, Fabian Karl; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Pre-service Primary School Teachers’ Preparation for Team-Teaching in Inclusive Schools. Poster Presentation. 18th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2019. „Thinking Tomorrows’s Education: Learning from the past, in the present and for the future" - Hoya, Fabian Karl; Löper, Marwin Felix; Schulze, Jan Roland; Mester, Theresa; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne; Hellmich, Frank

Depth camera based statistical shape fitting approach for the creation of an individualized lower body biomechanical model: validity and reliability - Taetz, Bertram; Teufl, Wolfgang; Weidmann, Alexander; Pietschmann, Juliane; Jöllenbeck, Thomas; Bleser, Gabriele (Computer Methods in Biomechanics and Biomedical Engineering)
Keywords: Computer Science Applications; Human-Computer Interaction; Biomedical Engineering; General Medicine; Bioengineering

Einblicke in Normalitätsvorstellungen von Lehramtsstudierenden - "Die Situation meines Förderkindes habe ich mit meiner eigenen verglichen und Mitleid gespürt" - Pieper, Catania; Kottmann, Brigitte (Lehren und Lernen)

„Raubdrucke“ als zeitgeschichtliche Dokumente der Kinderladenbewegung - Göddertz, Nina; Bock, Karin (Zugänge zur Kinderladenbewegung)
Im Forschungskontext der Kinderladenbewegung gehört es inzwischen zum Allgemeinplatz, die Lektürestile der Kinderladenakteur_innen quasi wie selbstverständlich (mit) zu wissen: Nicht nur publizierte Bücher und Texte, sondern insbesondere sog. „Ormit“-Kopien gehörten in den 1960er Jahren zum Standardrepertoire der intellektuellen Auseinandersetzungen, der Diskurse und Diskussionen um und über die „repressionsfreie Erziehung“, der „Anleitungen für eine revolutionäre Erziehung“, der Re-Lektüre von Texten von und über Vera Schmidt, Siegfried Bernfeld, Anna Freud und anderen. Diese Kopien sind als „Raubdrucke“ in das zeitgeschichtliche Narrativ um und über die Kinderladenbewegung eingegangen, genauer: Ebenso ‚revolutionär‘ wie der Lektüreinhalt sollte wohl auch die Lektüreform ihren Namen bekommen. Dabei bezeichneten die Kinderladenakteur_innen die heute sog. „Raubdrucke“ jedoch viel häufiger als Reprints oder Nachdrucke.
Keywords: Erziehung; Kinderladenbewegung; Sozialpädagogik